Comparative Genomics Reveals Evolution of a Beak Morphology Locus in a High-Altitude Songbird. (27th June 2020) - Cheng, Yalin; Miller, Matthew J; Zhang, Dezhi; Song, Gang; Jia, Chenxi; Qu, Yanhua; Lei, Fumin
Abstract: The Ground Tit ( Pseudopodoces humilis ) has lived on the Qinghai-Tibet Plateau for ∼5.7 My and has the highest altitudinal distribution among all parids. This species has evolved an elongated beak in response to long-term selection imposed by ground-foraging and cavity-nesting habits, yet the genetic basis for beak elongation remains unknown. Here, we perform genome-wide analyses across 14 parid species and identify 25 highly divergent genomic regions that are significantly associated with beak length, finding seven candidate genes involved in bone morphogenesis and remolding. Neutrality tests indicate that a model allowing for a selective sweep in the highly conserved COL27A1 gene best explains variation in beak length. We also identify two nonsynonymous fixed mutations in the collagen domain that are predicted to be functionally deleterious yet may have facilitated beak elongation. Our study provides evidence of adaptive alleles in COL27A1 with major effects on beak elongation of Ps. humilis .